Revista Litteraria do Gabinete de Leitura De Maroim (1890-1891) : subsídios para a história dos impressos em Sergipe - Silva, Maria Lúcia Marques Cruz e (2006)
This study has a general goal to analyse and to describe the Revista Litteraria Orgam do Gabinete de Leitura de Maroim" published between 1890 and 1891, in period of eight months as a struggle strategy by a group of intellectuals which belonged to the Cabinet and where at opposite endes to the publics government, regarding their cultural and politic representations. From the informations within the content and the typographic as well as the material resourses of the whole thirty-four editions in the process of prodution, circulation and apropriation it was not only posibile to acknowledge the profile of the authors which were more present but also the educational aim of the Cabinet, whish was in accordance to the concepts of apropriation, representation and materiality proposed by Roger Chartier, and to the Indictary Method proposed by Carlo Ginzburg. The analysis of textual corpus detected literaries produtions, discussions about New Pedagogy, scientificism, woman education, and politics inspired in republican beliefs. The ideological discussions caused the typography, where the magazine was printed, to close.